High genetic variation, low differentiation, and Pleistocene expansions of the migratory and endangered long-nosed tequila bat, Leptonycteris nivalis, inferred using both maternal and paternal genetic markers - Roberto-Emiliano Trejo-Salazar; Jaime Gasca-Pineda; Katia Hernández-Bolaños; Dulce-Carolina Hernández-Rosales; Rosalinda Tapia-López; Erika Aguirre-Planter; Rodrigo A. Medellín; Livia León-Paniagua; Luis E. Eguiarte (PLoS ONE, 2025)
Tequila bats (genus Leptonycteris) have gained attention for their critical role in pollinating different plant species, especially Agave spp. and columnar cacti. Leptonycteris nivalis is the largest nectar-feeding bat in the Americas, and the females exhibit migratory behavior during the breeding season. Due to its relatively small and seemingly declining population sizes, this species is protected by government agencies in the United States and Mexico. We conducted population genetics and phylogeographic analyses to elucidate the genetic structure and demographic history of the species using two mitochondrial markers and a Y chromosome-associated gene, to describe both maternal and paternal lineages. We estimated high haplotypic diversity measures for the different markers (Dloop—Hd = 0.775; Cyt-b—Hd = 0.937; DBY -Hd = 0.946). We found that geographic genetic differentiation is very low, and there is high connectivity among localities. The estimated divergence time between L. nivalis and L. yerbabuenae, the other species in the genus found in Mexico, aligns with previous estimates for the genus (6.91–9.43 mya). A demographic expansion was detected approximately at 600 ka—700 ka (thousands of years ago). The historical demographic changes observed in L. nivalis appear to be associated with environmental shifts during the Pleistocene, which likely impacted the distribution range of the plants that these bats feed on, such as Agave species.